HUBUNGAN HORMON PARATIROID, KALSIUM SERUM DENGAN BONE MINERAL DENSITY (BMD) PADA WANITA PERIMENOPAUSE DAN POSTMENOPAUSE - , Pratiwi Herowati; , dr. Windarwati, Sp.PK(K) ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The increase in human life a woman associated with loss of bone tissue called osteoporosis. Osteoporosis is a metabolic skeletal disease characterized by low bone mass and microarchitectural deterioration. Perimenopause and postmenopause women had greater risk to suffering osteoporosis. The dual energy X-ray absorptiometry (DEXA) is a gold standart for diagnose osteoporosis by measure bone mineral density (BMD), but had limited availability in hospitals. The process of osteoporosis is governed by a number of hormones, including estrogen. Another hormone associated with osteoporosis is parathyroid hormone that acts as a regulator of the balance of bone metabolism and pathophysiology associated with type 2 primary osteoporosis is due to low serum calcium balance. Changes in calcium ion concentration caused by the reduction in PTH levels, so that serum levels of PTH can be used as a marker of the status calcium in the body. The aim of this study is to understand the profile and the correlation of parathyroid hormone and serum calcium by a score of BMD in postmenopausal and perimenopouse women's groups. This is a cross-sectional study. The subject are women more than 45 years old. The parathyroid hormone measured by electrochemiluminescence immunoassay method. The DEXA method is used for measure BMD.